ChemInform Abstract: Iodine‐Mediated Copper‐Catalyzed Efficient α‐C(sp2)‐Thiomethylation of α‐Oxoketene Dithioacetals with Dimethyl Sulfoxide in One Pot. Issue 17 (April 2016) - Shukla, Gaurav; Srivastava, Abhijeet; Nagaraju, Anugula; Raghuvanshi, Keshav; Singh, Maya Shankar
Abstract: This operationally simple one‐pot protocol includes region‐defined consecutive iodination and sulfenylation of the challenging α‐C(sp 2 )—H bond of dithioacetals employing cheap and readily available reagents.